A Review on Pharmacological Activities of Calotropis Procera - Mali, Rohit P; Rao, Priya S; Jadhav, R. S. (Journal of Drug Delivery and Therapeutics, 2019)
The plant Calotropis procera (Aiton) Dryand belong to the Apocynaceae family it is popularly known as “Rui” in Marathi, “ Mudar” in hindi other common name include Rubber Bush, Apple of sodom. (India & Pakistan). The bark and leaves are known to show wound healing, shows anti-Hyperglycemic effect, Analgesic, Anti pyretic, neuromuscular blocking activity, Purgative, anti-cancer activities. The phytochemistry of plant reveals presence of triterpenoids, flavonoids, cardiac glycosides, cardenolides, anthocyanins, α-amyrin, β-amyrin, lupeol, β-sitosterol, flavanols, mudarine, resins, a powerful bacteriolytic enzyme calactin, a nontoxic proteolytic enzyme calotropin, and a wax was isolated from the heartwood of Calotropis procera. The present review focuses on pharmacological activities of Calotropis procera. Keywords: Calotropis procera, anti- Hyperglycemic effect, wound healing, pharmacological activities.